The Limits of the Client’s Will in Establishing a Legal Power of Attorney Without the Lawyer’s Acceptance: An Analytical Study of Omani Legislation and Practice in Comparison with Select Legislative Systems - Abdulaziz Mohammed Ramas Al-Rawas (International Journal of Law Research and Studies, 2026)
The judicial system in the Sultanate of Oman has undergone rapid technical transformations in recent years, most notably the adoption of the "Tawtheeq" electronic system, which allows the client to issue a legal power of attorney (POA) without the lawyer’s prior knowledge or explicit acceptance at the moment of creation. This study aims to clarify the legal regulation of the lawyer’s POA in Omani legislation and its adequacy in governing the relationship between the two parties, as well as resolving the legal issues arising from POAs issued by unilateral will. The study addresses the legal nature of the POA in the Civil Transactions Law and the professional specificity of the legal profession, highlighting emerging legal and ethical challenges—particularly the issue of "conflict of interest" and the impact of absent consent on the validity of judicial procedures. The study adopts descriptive, analytical, and comparative methodologies by reviewing the experiences of Kuwait, Bahrain, and Malaysia. The study concluded that the client’s unilateral issuance of a POA represents a fundamental flaw in the principle of contractual consent. It recommended the necessity of developing electronic systems to include immediate notifications to lawyers and requiring the client to formally notify the lawyer of the POA to ensure the meeting of wills and protect the independence of the legal profession.